Hand-Made Extra-Corporeal Knotting Versus Clip for Stump Closure in Laparoscopic Appendectomy: Hand-Made Extra-Corporeal Knotting and Stump Closure in Laparoscopic Appendectomy - Hassan, Haseeb Ul; Kiyani, Ziyad Afzal; Raja, Maryum Saleem; Shah, Syed Zakir Hussain; Zeeshan, .; Mumtaz, Fahad (Pakistan Journal of Health Sciences, 2026)
Acute appendicitis represents one of the most frequent surgical emergencies encountered in Pakistan. The delayed appendicitis and increased infection risks may impact postoperative outcomes and surgical decision-making. Objectives: To evaluate and compare hand-made extracorporeal knotting with polymeric clip closure in laparoscopic appendectomy, focusing on intraoperative performance measures and the incidence of early postoperative complications, including postoperative ileus, wound infection, and intra-abdominal infection within 15 days. Methods: A randomized controlled trial (NCT ID: 07281612) was carried out in the Department of Surgery, Abbas Institute of Medical Sciences, Muzaffarabad, over a period of twelve months. Using simple lottery-based random allocation, 190 patients diagnosed with uncomplicated acute appendicitis were recruited and assigned to either the hand-made extracorporeal knotting group (n=95) or the polymeric clip closure group (n=95). Relevant demographic, clinical, and intraoperative parameters were systematically documented. Results: The two groups demonstrated broadly comparable baseline profiles. However, the mean duration of surgery was modestly but significantly greater in the knotting group than in the clip group (45.8 ± 8.9 vs 42.8 ± 8.2 minutes; p=0.025). Intra-abdominal infection was observed in 1.1% of patients undergoing knotting compared with 6.3% of those receiving polymeric clips (p=0.049). On logistic regression, polymeric clip use was associated with increased odds of intra-abdominal infection (adjusted odds ratio 4.82; 95% confidence interval 1.01–22.73; p=0.048). Conclusions: Hand-made extracorporeal knotting results in a significantly lower rate of intra-abdominal infection compared to polymeric clip closure. Despite a modest increase in operative time, the knotting technique may offer a safer and more effective option for stump closure.